2020
DOI: 10.3389/fpsyg.2020.01331
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Conscious Deception Detection: When Reliance on False Deception Cues Contributes to Inaccurate Judgments

Abstract: People are generally too trusting, which decreases their ability to detect deceit. This suggests that distrust could enhance our deception detection abilities. Yet, a state of distrust may induce deliberative conscious thought. This mode of thinking has been related to worse complex decision making. Hence, we investigate whether contextual distrust decreases the ability to detect deceit via the stronger reliance on consciously held beliefs about which cues betray deception. In two studies, participants were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 80 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…We found that warning people about the chances of deception reduced, but did not eliminate, truth-bias (McCornack and Levine, 1990; also see replication by Kim and Levine, 2011). Although Stel et al (2020) did not forewarn participants, conceptually forewarning should lead to distrust as Stel et al define it. My understanding of our 1990 findings changed a decade later when Hee Sun Park came up with the "veracity effect" (Levine et al, 1999). Suspicion/distrust decreases accuracy for truths, increases accuracy for lies, and the gains and losses average out overall (Kim and Levine, 2011).…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…We found that warning people about the chances of deception reduced, but did not eliminate, truth-bias (McCornack and Levine, 1990; also see replication by Kim and Levine, 2011). Although Stel et al (2020) did not forewarn participants, conceptually forewarning should lead to distrust as Stel et al define it. My understanding of our 1990 findings changed a decade later when Hee Sun Park came up with the "veracity effect" (Levine et al, 1999). Suspicion/distrust decreases accuracy for truths, increases accuracy for lies, and the gains and losses average out overall (Kim and Levine, 2011).…”
Section: Introductionmentioning
confidence: 65%
“…Stel et al ( 2020 , p. 1) wrote: “distrust especially hampers the detection of truth, which is partly due to more reliance on false beliefs about deception cues. These results corroborate the idea that deliberative conscious information processing may hinder truth detection, while intuitive information processing may facilitate it” (see Street and Vadillo, 2016 for a discussion of unconscious and indirect lie detection).…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations